2019
DOI: 10.1093/ageing/afz159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radial extracorporeal shockwave therapy on spasticity of upper-limb agonist/antagonist muscles in patients affected by stroke: a randomized, single-blind clinical trial

Abstract: Background the effects of radial extracorporeal shock wave therapy (rESWT) were assessed on agonist/antagonist muscles in stroke patients with elbow spasticity, the duration of effects and influence on function. Methods patients were randomly assigned into groups: control (A, n = 25), rESWT on agonist muscles (B, n = 27) and rESWT on antagonist muscles (C, n = 30) groups. Conventional physical therapy was given to three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 20 publications
0
45
0
1
Order By: Relevance
“…The PRISMA diagram (see Figure 1) summarizes the results of the scientific literature search. Sixteen randomized controlled trials were included: these were by Bae et al, 15 Santamato et al, 16 Fouda et al, 17 Dymarek et al, 18 Kim et al, 19 Li et al, 20 Yoon et al, 21 Duan et al, 22 Guoxing et al, 23 Guo et al, 24 Fouda et al, 25 Kamaluddin et al, 26 Park et al, 27 Wu et al, 28 Ahmed et al, 29 and Li et al 30 Studied identified but not included are shown in Appendix 2. No author responded when contacted for additional information.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PRISMA diagram (see Figure 1) summarizes the results of the scientific literature search. Sixteen randomized controlled trials were included: these were by Bae et al, 15 Santamato et al, 16 Fouda et al, 17 Dymarek et al, 18 Kim et al, 19 Li et al, 20 Yoon et al, 21 Duan et al, 22 Guoxing et al, 23 Guo et al, 24 Fouda et al, 25 Kamaluddin et al, 26 Park et al, 27 Wu et al, 28 Ahmed et al, 29 and Li et al 30 Studied identified but not included are shown in Appendix 2. No author responded when contacted for additional information.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported brain area stroke. 28 Most patients were in the chronic phase (>six months) except in the studies by Duan et al, 22 Guoxing et al, 23 Kamaluddin et al 26 which were in the subacute phase, Guo et al, 24 which were in late phase and Li et al 30 included both. All the studies included patients with a Modified Ashworth Scale 31 muscle spasticity score ⩾ 1, and excluded patients with fixed muscle contractures = 4 score points.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations